2021
DOI: 10.1093/gji/ggab077
|View full text |Cite
|
Sign up to set email alerts
|

Application of the differential effective medium theory to determine fluid saturation and crack density from measured P- and S-wave velocities

Abstract: Summary The differential effective medium (DEM) theory studied in this article describes elastic moduli of a fractured medium with help of differential equations, where crack density is the independent variable and fluid saturation is a parameter. The effective medium is isotropic for randomly oriented flat ellipsoidal cracks and thus fully characterized by two elastic constants. In this article we derive an analytical solution of the equation for Poisson’s ratio and we transform the differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Zillmer et al. (2021) computed the crack density from full waveform sonic logging measurements on F1, describing the crack density as the number of cracks multiplied by the mean volume occupied by an ellipsoidal crack, per unit volume. It is showed that the crack density has average values of 0.5 from 38 m to 55 m depths, reaches a maximum of 0.8–1.0 around 64 m depth and decreases to 0.3 below, until depths of 80 m, suggesting that the unweathered granitic basement is not reached in the deepest borehole.…”
Section: Study Site and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Zillmer et al. (2021) computed the crack density from full waveform sonic logging measurements on F1, describing the crack density as the number of cracks multiplied by the mean volume occupied by an ellipsoidal crack, per unit volume. It is showed that the crack density has average values of 0.5 from 38 m to 55 m depths, reaches a maximum of 0.8–1.0 around 64 m depth and decreases to 0.3 below, until depths of 80 m, suggesting that the unweathered granitic basement is not reached in the deepest borehole.…”
Section: Study Site and Methodologymentioning
confidence: 99%
“…Moreover, Zillmer et al. (2021) showed that most cracks between 40 m and 80 m depth are water‐saturated.…”
Section: Study Site and Methodologymentioning
confidence: 99%